STRATEGIES FOR RELIGIOUS CONFLICT RESOLUTION IN INDONESIA: A CASE STUDY OF THE JA’FARIYAH SHI’A MINORITY IN TERNATE - Fatum Abubakar; Zaenal Muttaqin; Salimah Muhammed Husayn; Dian Nur Anna (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
This study aims to describe and analyse the relationship between religious groups, societies, and governments, as well as strategies for managing religious conflict, with a case study of the Ja'fariyah Shi'a minority group in Moya, Ternate. The Shi'a community led by Nawawi Husni, according to the Jema'ah Ahlul Bait Indonesia (IJABI), is considered to have different religious teachings and practices and is judged to be inconsistent with the teachings of the Shi'a in general. In addition to having a layered complexity, the existence of this community is also considered misguided, so it is often the target of the intolerance of other religious groups, even by the local government. Through a qualitative approach using a sociological perspective, the results of this study revealed that the silent (non-reactive) attitude of the Ja'fariyah Shi'a group in responding to various rejections and misconceptions about its group is not passive. Instead, they choose to do "resistance" creatively by using the media to counter negative opinions against them. The choice of this "resistance" model is not separate from the role and position of Husni Nawawi in attracting the government's interests. Consider that the pattern of hard-power conflict approaches must change to the smart-power transformation model.